The fate of terrestrial biodiversity during an oceanic island volcanic eruption - Manuel Nogales; María Guerrero-Campos; Thomas Boulesteix; Noémie Taquet; Carl Beierkuhnlein; Robin Campion; Silvia Fajardo; Nieves Zurita; Manuel Arechavaleta; Rafael García; Frank Weiser; Félix M. Medina (Scientific Reports, 2022)
Abstract Volcanic activity provides a unique opportunity to study the ecological responses of organisms to catastrophic environmental destruction as an essential driver of biodiversity change on islands. However, despite this great scientific interest, no study of the biodiversity at an erupting volcano has yet been undertaken. On La Palma (Canary archipelago), we quantified the main species affected and their fate during the 85-day eruption (September–December 2021). Our main objective consisted of monitoring the biodiversity subjected to critical stress during this volcanic eruption. We found that all biodiversity within a 2.5 km radius was severely affected after the first two weeks. It is challenging to assess whether volcanism can drive evolutionary traits of insular organisms. Examples are the adaptation of an endemic conifer to high temperatures, selection of functional plant types—secondary woodiness—, effects of the disappearance of invertebrates and their influence in trophic nets and vertebrate trophic plasticity. However, our data suggest that such previous evolutionary changes might continue to favour their resilience during this eruption. Lastly, it is a very good opportunity to assess the extent to which these periodic volcanic catastrophes may constitute temporary windows of repeated opportunities for the evolution and speciation of oceanic island biota.